Neck muscle endurance and head posture: A comparison between adolescents with and without neck pain. (April 2016) - Oliveira, Ana Carolina; Silva, Anabela G.
Abstract: Objective: The main aims of this study were to compare the neck flexor and extensor endurance and forward head posture between adolescents with and without neck pain. The secondary aims were to explore potential associations between muscles endurance, head posture and neck pain characteristics and to assess intra-rater reliability of the measurements used. Methods: Adolescents with neck pain (n = 35) and age-matched asymptomatic adolescents (n = 35) had their forward head posture, neck flexor endurance and neck extensor endurance measured using clinical tests. Intra-rater reliability was also assessed. Results: Forward head posture and neck flexor and extensor endurance tests showed moderate to almost perfect intra-rater reliability (ICC between 0.58 and 0.88). Adolescents with neck pain showed significantly less forward head posture (neck pain = 46.62 ± 4.92; asymptomatic = 44.18°± 3.64°, p > 0.05) and less neck flexor (neck pain = 24.50 ± 23.03s; asymptomatic = 35.89 ± 21.53s, p > 0.05) and extensor endurance (neck pain = 12.6.64 ± 77.94s; asymptomatic = 168.66 ± 74.77s, p > 0.05) than asymptomatic adolescents. Conclusions: Results suggest that changes in posture and neck muscle endurance are a feature of adolescents with neck pain. Highlights: Neck pain in adolescents is of considerable duration and frequency. Neck pain in adolescents interferes with daily activities. Adolescents with neck pain have decreased neck flexor endurance capacity. Adolescents with neck pain have decreased neck extensor endurance capacity. There is a need for early interventions targeting adolescents with neck pain.